A Method for Reconstructing the Past Soil Temperature Based on Tree-Ring Widths. Issue 4 (5th February 2020) - Yuan, Shuai; Zheng, Yonghong; Qi, Yongdong; Kong, Fanxi; Wang, Dan; Zhang, Fangfang
Abstract: Soil temperature can affect tree growth and is one of the most important types of basic data for forest cultivation and management. To obtain a long-term time series of soil temperatures, we explored the utility of dendroclimatology in a subtropical area of China. In this study, the relations between tree-ring-width chronologies and climate factors were explored by correlation analysis. The results indicated that the limiting climatic factors for the radial growth of Huangshan pine were elevation-specific. Further investigation found that chronology at high elevations was significantly correlated with soil temperature. Then, we described a reconstruction of the soil temperatures of the Dabie Mountains area using the tree-ring width chronology from 1869 to 2015 and showed that the reconstruction explained 42.9 percent of the instrumental soil temperature variation in the common years. We found that the 1970s and 2000s were the coldest and warmest decades since 1884, respectively. The results of the reconstruction method for describing past soil temperatures can provide a reference for other subtropical forests. Furthermore, the results of our research also have a certain significance for guiding policymaking related to forest cultivation and management.